Niger : Staff Report for the 2006 Article IV Consultation and Third Review Under the Three- Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver and Modifications of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the 2006 Article IV Consultation and Third Review Under the Poverty Reduction and Growth Facility for Niger. Macroeconomic performance and policy implementation have been broadly satisfactory. After a drought in 2004, a bumper harvest in late 2005 and good rains in 2006 have helped economic recovery, improved food security, and eased inflation. The fiscal deficit in 2006 is expected to be narrower than programmed, reflecting mainly lower spending on investment and food security.